Control of Carbapenem-resistant Enterobacteriaceae, Acinetobacter baumannii, and Pseudomonas aeruginosa in Healthcare Facilities: A Systematic Review and Reanalysis of Quasi-experimental Studies. (23rd November 2018) - Tomczyk, Sara; Zanichelli, Veronica; Grayson, M Lindsay; Twyman, Anthony; Abbas, Mohamed; Pires, Daniela; Allegranzi, Benedetta; Harbarth, Stephan
Abstract: Carbapenem-resistant Enterobacteriaceae (CRE), Acinetobacter baumannii (CRAB), and Pseudomonas aeruginosa (CRPsA) are a serious cause of healthcare-associated infections, although the evidence for their control remains uncertain. We conducted a systematic review and reanalysis to assess infection prevention and control (IPC) interventions on CRE-CRAB-CRPsA in inpatient healthcare facilities to inform World Health Organization guidelines. Six major databases and conference abstracts were searched. Before-and-after studies were reanalyzed as interrupted time series if possible. Effective practice and organization of care (EPOC) quality criteria were used. Seventy-six studies were identified, of which 17 (22%) were EPOC-compatible and interrupted time series analyses, assessing CRE (n = 11; 65%), CRAB (n = 5; 29%) and CRPsA (n = 3; 18%). IPC measures were often implemented using a multimodal approach (CRE: 10/11; CRAB: 4/5; CRPsA: 3/3). Among all CRE-CRAB-CRPsA EPOC studies, the most frequent intervention components included contact precautions (90%), active surveillance cultures (80%), monitoring, audit and feedback of measures (80%), patient isolation or cohorting (70%), hand hygiene (50%), and environmental cleaning (40%); nearly all studies with these interventions reported a significant reduction in slope and/or level. The quality of EPOC studies was very low to low. Abstract : A systematic review and reanalysis found that infection prevention and control strategies including contact precautions, active surveillance cultures, monitoring, audit and feedback, patient isolation or cohorting, hand hygiene, and environmental cleaning were critical to the control of nosocomial carbapenem-resistant Enterobacteriaceae, Acinetobacter baumannii, and Pseudomonas aeruginosa .